Penggunaan Teknik Persuasif pada Kalimat yang Mempresentasikan Kota Jakarta dalam Website Pariwisata (www.indonesia.travel/id/id/home) Versi Bahasa Indonesia - Iswandi, Fedro; Nopiyadi, Dwi; Nugraha, Tria Aditia (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
Before translating, translators need to observe the process of translation and one of them is source language text analysis. Therefore, the purpose of research is to identify persuasive technique that it is used by writer to present a Jakarta city in tourism website. The approach of this research is qualitative descriptive. Then, the data is sentences that contain persuasive language and the source of data is tourism website (www.indonesia.travel/id/id/home) Indonesian version. Furthermore, data is collected through documentation and note taking technique after that data is analyzed by (Miles, MB., Huberman & Saldana, 2014) and Keraf (2004) theory. The result showed that the uses of rationalization persuasive technique is more dominant (17 data) than identification persuasive technique (10 data). It can be concluded that the writer attempted to persuade audiences (tourists) through the fact and truth about tourism destination of Jakarta city. Next, it will be consideration for translators. Thus, text (tourism website) contains persuasive language so that there will be analysis step before translating the text (Indonesian into English version).  Keywords: Source Text Analysis, Persuasive Technique, Tourism Website,                   Jakarta City